Comparative study of the taphonomic history of Holocene gastropods and ostracods of the high basin of the Salado river, Buenos Aires, Argentina - Pisano, María Florencia (2022)
Gastropods and ostracods are widely used in Quaternary paleoenvironmental reconstructions but the taphonomic studies that should precede them are not as common. In this paper we compare the taphonomic information obtained from assemblages recovered in Holocene fluvial sequences of the Salado River basin (Buenos Aires, Argentina) and analyze the changes or similarities between species, localities and stratigraphic units. Using taphonomic grades, gastropod shells were cataloged based on three attributes: fragmentation, discoloration and dissolution. For ostracods, discoloration and dissolution together with the population structure (adults-juveniles A/J, valves-carapace V/C and male-female ratios) were analyzed. For gastropods, Heleobia parchappii, Biomphalaria peregrina and Succinea meridionalis showed similar preservation patterns, and Miradiscops brasiliensis showed least evidence of alteration. In ostracods, these patterns varied among species. For V/C ratio, 7% of assemblages were formed only by valves, 82% were dominated by valves and 11% were dominated by carapaces. Fragmentation and population structure allowed autochthonous and allochthonous associations to be distinguished. Gastropod assemblages with low levels of fragmentation were recovered mainly from the uppermost levels of the stratigraphic profiles. For ostracods, the A/J ratio showed that 52% of the assemblages were dominated by adults with most ontogenetic stages represented and 29% retained their original population structure suggesting they would be autochthonous associations, whereas 19% of the assemblages were dominated by juvenile valves therefore assuming allochthonous associations. Our results indicate that taphonomic analysis is an effective tool that allows identifying autochthonous assemblages, which are the most reliable for robust paleoenvironmental reconstructions.